2008
DOI: 10.1063/1.2946703
|View full text |Cite
|
Sign up to set email alerts
|

Stochastic surrogate Hamiltonian

Abstract: The surrogate Hamiltonian is a general scheme to simulate the many body quantum dynamics composed of a primary system coupled to a bath. The method has been based on a representative bath Hamiltonian composed of two-level systems that is able to mimic the true system-bath dynamics up to a prespecified time. The original surrogate Hamiltonian method is limited to short time dynamics since the size of the Hilbert space required to obtain convergence grows exponentially with time. By randomly swapping bath modes … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
58
0

Year Published

2010
2010
2018
2018

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 45 publications
(59 citation statements)
references
References 35 publications
1
58
0
Order By: Relevance
“…Longer propagation times than those computationally affordable with exact dynamics of system and environment become possible by separating the environment into two baths, one that is responsible for the memory effects and that is modeled by effective modes as explained above, and a second one that by itself would lead to Markovian dynamics only. The secondary bath can be accounted for in terms of a Markovian master equation in Lindblad form [38,70] or via a stochastic unravelling using a single secondary bath mode [71]. A more comprehensive overview over methods to tackle non-Markovian dynamics is found in Ref.…”
Section: A Markovian Vs Non-markovian Dynamicsmentioning
confidence: 99%
“…Longer propagation times than those computationally affordable with exact dynamics of system and environment become possible by separating the environment into two baths, one that is responsible for the memory effects and that is modeled by effective modes as explained above, and a second one that by itself would lead to Markovian dynamics only. The secondary bath can be accounted for in terms of a Markovian master equation in Lindblad form [38,70] or via a stochastic unravelling using a single secondary bath mode [71]. A more comprehensive overview over methods to tackle non-Markovian dynamics is found in Ref.…”
Section: A Markovian Vs Non-markovian Dynamicsmentioning
confidence: 99%
“…However, challenges in understanding electronic decoherence have arisen from recent spectroscopic observations that have demonstrated that in some photosynthetic systems electronic coherences can be longlived [13][14][15], with lifetimes exceeding 400-600 fs. These results have lead to discussions of the role of quantum coherences in biological processes and reconsideration of our understanding of decoherence dynamics in single molecules and molecular aggregates [3,[13][14][15][16][17][18][19][20][21][22][23][24]. Many of the associated computations utilize phenomenological models or master equations [25] that approximate the dynamical effects of the bath on the system coordinates without explicitly following the bath dynamics.…”
Section: Introductionmentioning
confidence: 99%
“…As demonstrated earlier (18), this dynamic disorder helps the hole density to overcome the potential barrier created by the electrostatic interactions between the propagating positive charge and the anion S − a . To simulate the dissipative dynamics of the propagating hole, a stochastic surrogate Hamiltonian (SSH) scheme was used (47,(51)(52)(53)(54). The SSH approach is based on the numerical propagation of a multiparticle density matrix that accounts for the degrees of freedom associated with the propagating charge and a few phonon modes (47) (details are provided in SI Text).…”
mentioning
confidence: 99%